2000
DOI: 10.1002/1520-7560(2000)9999:9999<::aid-dmrr141>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Why is learning and memory dysfunction in Type 2 diabetes limited to older adults?

Abstract: Review of the literature on the cognitive correlates and consequences of Type 2 diabetes reveals two very intriguing findings. Not only are verbal learning and memory skills most likely to be disrupted as compared to other cognitive skills (e.g. attention, executive function; psychomotor efficiency), but these mnestic deficits appear to be restricted to individuals with diabetes who are older than 60-65 years of age. Middle-aged adults with either Type 2 or Type 1 diabetes are apparently protected insofar as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
119
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 97 publications
(83 reference statements)
9
119
2
1
Order By: Relevance
“…Many studies confirmed that sustained hyperglycemia, indicated by elevated HbA1c, is an independent risk factor for the cognitive impairment [39]. Other researchers also noticed that ghrelin levels in obesity patients was lower compared to agematched controls health people [40], and they are negatively correlated with BMI [9,41].…”
Section: Discussionsupporting
confidence: 92%
“…Many studies confirmed that sustained hyperglycemia, indicated by elevated HbA1c, is an independent risk factor for the cognitive impairment [39]. Other researchers also noticed that ghrelin levels in obesity patients was lower compared to agematched controls health people [40], and they are negatively correlated with BMI [9,41].…”
Section: Discussionsupporting
confidence: 92%
“…Research on type 2 diabetes suggests that there may be an interaction between age and the severity of cognitive problems: cognitive deficits appear to be more pronounced in individuals who are Ͼ60 -65 years of age (49). Thus far, no studies have addressed the effects of type 1 diabetes on cognition in individuals of more advanced age.…”
Section: Conclusion -mentioning
confidence: 99%
“…This latter group has an increased risk of cognitive impairment [3], which may be associated with insulin therapy [4,5]. Since the association between diabetes and cognitive impairment appears confined to middle-aged or older individuals [6], the ageing brain could be particularly susceptible to neuroglycopenia. The interpretation of studies examining the relationship between blood glucose-lowering therapies, hypoglycaemia and cognitive function in type 2 diabetes is, however, complicated by factors other than age, such as duration of diabetes and of insulin treatment, comorbidities, including renal insufficiency, and polypharmacy [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%